"And They Knew They Were Naked": The Mortification of the Black Body. (May 2020) - Lindsay, Michael
While it may be characterized as the inception of freedom for the colonizing and imperial-minded European, America represents a great tribulation for the enslaved African, kidnapped and sold an ocean away from his homeland, and it can be characterized as an all-out assault on African peoples' bodies, culture, and minds. Though the economic interest of Europeans was the impetus for the African Holocaust, European Christian theology has consistently offered religious justification for the inhumane practices of the oppression of Black people—making the fight for freedom, in part, a religious battle. Insomuch, White supremacy is held together by a version of Christianity that venerates whiteness as its most divine ideal. This study explores the religious conundrum that Black people face by reexamining biblical text to connect the sacred and secular experiences of Black people to their social predicament. Apostle Paul's idea of mortification in Colossians 3:5 and the theory of mortification as intrinsic to the idea of order are connected in order to critique the complex system of religious racism and illustrate the impossibility of freedom under current circumstances. In addition, the theory of social death and the theory of the death-bound-subject are utilized to interpret the Black experience in America, in part, as a battle for spiritual survival in an anathematic state of being. Ultimately, this study concludes that it is the formulation of White supremacy, and not the execution of White supremacy, that places Blacks in confrontation with death (physically and spiritually), and this confrontation has deeply religious underpinnings.